Social Cohesion and Refugee-Host Interactions : Evidence from East Africa - Betts, Alexander; Stierna, Maria Flinder; Omata, Naohiko; Sterck, Olivier (World Bank, Washington, DC, 2022)
Building upon the literature on contact theory, this paper explores the role of inter-group interaction in shaping social cohesion between refugees and host communities in East Africa. It draws upon ﬁrst-hand quantitative (n=16,608) and qualitative data collected from refugees and nearby host communities in urban and camp-like contexts in Ethiopia, Kenya, and Uganda. Focusing on the Uganda data, OLS regressions reveal a positive and signiﬁcant correlation between refugee-host interaction and the perception of hosts towards refugees. This association disappears when an instrumental variable (IV) approach is used to address endogeneity issues, except when only data from the urban context is used. The analysis of cross-country data highlights further diﬀerences in the types of interaction and perception that matter between urban and camp-like contexts. It also suggests that ethno-linguistic proximity between refugee and host populations is associated with more positive attitudes. In all contexts, an important part of attitude formation appears to take place at the intra-group level, within households and immediate neighbourhoods, independently of individual interaction with the out-group. The paper proposes a series of policy recommendations to improve refugee-host social cohesion, with diﬀerent approaches required in urban and camp-like contexts.